Allelopathic Inhibition of Nitrifying Bacteria by Legumes - Umiyati, Uum (JOURNAL OF TROPICAL SOILS, 2017)
The study aimed at understanding the competitive ability of legumes Vigna radiata L. and Mucuna pruriens with weeds and their effects on the activity of nitrifying bacteria in soils and the contents of organic-N in legumes and weeds. The experiment was arranged in a randomized block design with three factors and four replications. The first factor was soil order, i.e. Inceptisol and Vertisol; the second factor was types of legumes, i.e. Vigna radiata L. cultivar Sriti and Mucuna pruriens; and the third factor was weed management, i.e. with weed management and without weed management. The results showed that Vigna radiata L. and Mucuna pruriens indirectly influence the supply of available nitrogen in soils that can be taken up by the coexisted plants or weeds via the inhibition of the growth of Nitrosomonas and Nitrobacter in soils. As a results, the organic-N content in weeds decreases, which is in contrast to the increasing amount of organic-N in Vigna radiata L. and Mucuna pruriens. The results indicated that Vigna radiata L. and Mucuna pruriens are considered as allelophatic legumes, resulting in low organic-N content in weeds.Â Â Keywords: Allelopathic, Mucuna pruriens, Nitrosomonas, Nitrobacter, Vigna radiataÂ